Trust in cooperation or ability? An experimental study on gender differences - Christiane Schwieren; Matthias Sutter (University of Innsbruck, Department of Public Finance, 2007)
We examine gender differences in trust in another party's cooperation (CC) or its ability (AC). While men and women do not differ concerning trust in cooperation, gender has a strong influence when trust in another subject's ability is required.
Keywords: C72; C91; 330; trust; gender; experiment; cooperation; ability; stereotypes; Verhaltensökonomik; Vertrauen; Geschlecht; Test; Theorie; Nichtkooperatives Spiel